2017
DOI: 10.1093/restud/rdx030
|View full text |Cite
|
Sign up to set email alerts
|

The Analytics of SVARs: A Unified Framework to Measure Fiscal Multipliers

Abstract: Does scal policy stimulate output? SVARs have been used to address this question but no stylized facts have emerged. We derive analytical relationships between the output elasticities of scal variables and scal multipliers. We show that standard identi cation schemes imply different priors on elasticities, generating a large dispersion in multiplier estimates. We then use extra-model information to narrow the set of empirically plausible elasticities, allowing for sharper inference on multipliers. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 45 publications
15
66
1
Order By: Relevance
“…It is well known from the fiscal policy literature (Caldara and Kamps, 2017) that the restriction on the output elasticity of policy is crucial for the identification of policy shocks. For this reason, we provide a thorough robustness analysis of our findings towards restrictions on this elasticity.…”
Section: Identification Of Stw Policy Shocksmentioning
confidence: 99%
“…It is well known from the fiscal policy literature (Caldara and Kamps, 2017) that the restriction on the output elasticity of policy is crucial for the identification of policy shocks. For this reason, we provide a thorough robustness analysis of our findings towards restrictions on this elasticity.…”
Section: Identification Of Stw Policy Shocksmentioning
confidence: 99%
“…An alternative, not pursued here, would be to work with sign restrictions. For an analysis of sign restrictions in fiscal VARs and their implications for the implied fiscal elasticities, see Caldara and Kamps ().…”
mentioning
confidence: 99%
“…Some studies regress output on historical exogenous tax changes identified with the Romer-and-Romer narrative approach (Romer and Romer 2010;Favero and Giavazzi 2012). Other studies estimate the causal effect of tax changes on output with instrumental-variable methods, using as instruments either some estimates of exogenous tax shocks (Blanchard and Perotti 2002;Caldara and Kamps 2017), or the historical exogenous tax changes identified with the Romer-and-Romer narrative approach (Barro and Redlick 2011;Ravn 2013 and2014). Another method is to identify tax shocks with sign restrictions on the impulse responses of vector autoregressions (Mountford and Uhlig 2009).…”
Section: Introductionmentioning
confidence: 99%